Factors associated with improvement in oral fluency when using video‐synchronous mediated communication with native speakers. (23rd January 2019) - Spring, Ryan; Kato, Fumie; Mori, Chikako
Abstract : Computer‐mediated, communication‐based foreign language learning programs are showing great promise. Among these, video‐synchronous mediated communication seems to offer an effective way to provide speaking practice, although research findings have been inconclusive. Furthermore, among studies that have documented the effectiveness of video‐mediated communication, it is not clear why some learners improve more than others. This study reports data from three separate learner groups who engaged in video‐synchronous mediated communication with native speakers. Specifically, the study investigated its effectiveness on learners' oral fluency and explored the impact of enjoyment, target language speaking time, and instructional level on improvement. The data suggest that participation did not necessarily guarantee greater improvement when compared with students in a control group; that instructional level is associated with improvement; that allocated time is associated with a decrease in pausing; and that students' reasons for enjoying the program, rather than their overall enjoyment, are related to improvement. The Challenge: Technology increasingly offers opportunities for language learners to engage with others. Does video‐synchronous mediated communication with native speakers offer an effective way to improve oral fluency? What factors are most strongly associated with increased fluency?